Uses of Innovative Modeling Tools within the Implementation of the Marine Strategy Framework Directive - Lynam, Christopher P.; Uusitalo, Laura; Patrício, Joana; Piroddi, Chiara; Queirós, Ana M.; Teixeira, Heliana; Rossberg, Axel G.; Sagarminaga, Yolanda; Hyder, Kieran; Niquil, Nathalie; Möllmann, Christian; Wilson, Christian; et al. (Frontiers in Marine Science, 2016)
In Europe, and around the world, the approach to management of the marine environment has developed from the management of single issues (e.g. species and/or pressures) towards holistic Ecosystem Based Management that includes aims to maintain biodiversity and protect ecosystem functioning. Within the European Union, this approach is implemented through the Marine Strategy Framework Directive (MSFD, 2008/56/EC). Integrated Ecosystem Assessment is required by the Directive in order to assess Good Environmental Status (GES). Ecological modeling has a key role to play within the implementation of the MSFD, as demonstrated here by case studies covering a range of spatial scales and a selection of anthropogenic threats. Modeling studies have a strong role to play in embedding data collected at limited points within a larger spatial and temporal scale, thus enabling assessments of pelagic and seabed habitat. Furthermore, integrative studies using food web and ecosystem models are able to investigate changes in food web functioning and biodiversity in response to changes in the environment and human pressures. Modeling should be used to: support the development and selection of specific indicators; set reference points to assess state and the achievement of GES; inform adaptive monitoring programs and trial management scenarios. The modus operandi proposed shows how ecological modeling could support the decision making process leading to appropriate management measures and inform new policy.